2019
DOI: 10.1186/s43008-019-0016-4
|View full text |Cite
|
Sign up to set email alerts
|

How to resolve cryptic species of polypores: an example in Fomes

Abstract: Species that cannot be easily distinguished based on morphology, but which form distinct phylogenetic lineages based on molecular markers, are often referred to as cryptic species. They have been proposed in a number of fungal genera, including the basidiomycete genus Fomes. The main aim of this work was to test new methods for species delimitation in cryptic lineages of polypores, and to define useful characters for species identification. A detailed examination of a number of different Fomes strains that had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 51 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…At present, we are still far from knowing the full extent of fungal diversity. One major finding based on DNA sequences over the last two decades has been the existence of multiple genetically divergent cryptic species within many previously defined species [ 61 , 62 , 63 , 64 , 65 ]. Within NTF, morphology-based classifications of strains and species have also likely underestimated the true magnitude of species diversity in this group of fungi.…”
Section: Discussionmentioning
confidence: 99%
“…At present, we are still far from knowing the full extent of fungal diversity. One major finding based on DNA sequences over the last two decades has been the existence of multiple genetically divergent cryptic species within many previously defined species [ 61 , 62 , 63 , 64 , 65 ]. Within NTF, morphology-based classifications of strains and species have also likely underestimated the true magnitude of species diversity in this group of fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Species identification in Agaricales has traditionally relied on morphological characters (e.g., Singer 1986;Bas et al 1988;Horak 2005;Knudsen and Vesterholt 2008) that are known to be subject to parallel evolution and phenotypic plasticity (Slepecky and Starmer 2009). In many cases, separation of species based on morphology alone is challenging and many taxa represent complexes with (pseudo)cryptic species (Geml et al 2006;Bickford et al 2007;Carriconde et al 2008;Stefani et al 2014;Balasundaram et al 2015;Guo et al 2016;Sánchez-García et al 2016;Li et al 2017;Peintner et al 2019;Vizzini et al 2019a, b;Nilsen et al 2020;Sato et al 2020;Voitk et al 2020). Putative interspecific hybridization events have been suggested to occur in some Agaricales (Aanen et al 2000;Hughes et al 2013).…”
Section: Species Concepts and Species Recognitionmentioning
confidence: 99%
“…In addition to molecular phylogenetic analyses and morphological study of basidiomata and mycelia, Peintner et al (2019) studied growth characteristics, carried out enzyme assays, and comparatively analyzed volatile compounds in order to resolve cryptic species in Fomes fomentarius s.l. These authors found that the hymenophore pore diameter and the diameter of skeletal hyphae are taxonomically valuable features if measured from statistically relevant structures.…”
Section: Species Concepts and Species Recognitionmentioning
confidence: 99%
“…Thus, having a reliable DNA sequence-based identification for these mushrooms is essential for their correct identification. Indeed, molecular studies have recently shown the existence of many ‘‘cryptic’’ fungal species, which cannot be distinguished morphologically [ 13 , 31 , 32 , 33 ], stressing that molecular information is indispensable for the identification and description of these species and indeed fungal species in general. The internal transcribed spacers (ITSs) of nuclear ribosomal RNA repeat units have frequently been used to identify fungal species.…”
Section: Introductionmentioning
confidence: 99%